Using the Augmented Reality to Teach of Global Reading of Preschoolers with Autism Spectrum Disorders - Таміла Коломоєць; Дар'я Кассім (Academy of Cognitive and Natural Sciences, 2018)
Kolomoiets N.H., Kassim D.A. Using the Augmented Reality to Teach of Global Reading of Preschoolers with Autism Spectrum Disorders. Over the last decade a significant increasing of the number of children with autism spectrum disorders (ASD) in the world is marked. Ukraine is no exception. High rates of disease ASD require finding the new ways of correcting these groups of children. The aim of the research: to substantiate feasibility of using of the augmented reality's technologies to teach of global reading in a special education of autistic children. In the course of the study an experiment, descriptive and comparative analysis methods, generalization, logical research method were used. Results of the research: it is shown that, it is expedient to use  technologies of the augmented reality in the educational and correctional process of children with ASD to teach them of global reading. Using the augmented reality reveals a number of new opportunities, the promising of which is an interaction with the artificial world through mobile devices, which are more accessible and predictable for the special development of autistic children. At the initial stage of teaching of global reading, the instrument of augmented reality is used in a set of successive task groups. The first of these is aimed at the development of visual perception, the formation of the ability to analyze, isolate and generalize, navigate in space. The second and third set of tasks included the teaching of children to understand the meaning of words, the correlation of words with images presented on the screen of gadgets. At the final stage, namely, teaching of global reading, the technology of augmented reality has opened unlimited possibilities for using of various text materials and virtual images to them. Conclusions: a) an analysis of experimental work with preschoolers with ASD suggests that the use of augmented reality in teaching of global reading of children helps to increase the efficiency of the educational and correctional process; b) the technology of the augmented reality has allowed rising to a qualitatively new level of mastering of global reading by autistic children; c) prospects for further experimental research will be the implementation of the proposed methodology and obtaining its effectiveness and efficiency in practice.